Kidney disease in children: latest advances and remaining challenges - Bertram, John F.; Goldstein, Stuart L.; Pape, Lars; Schaefer, Franz; Shroff, Rukshana C.; Warady, Bradley A. (Nature reviews. Nephrology, 2016)
In this Viewpoint, six leading researchers reflect on progress made in their specialist field of paediatric kidney disease. They provide their insight as to the direction research will take in future years, and comment on areas in which additional research or initiatives are required to improve renal outcomes and patient care for the paediatric and neonatal population.